ANGIOTENSIN CONVERTING ENZYME INHIBITORS IN THE THERAPEUTIC CLINIC - MaltsevaМ.S.; Martymianova, L.O.; VlasenkoО.O.; Savchenko, V.M. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The clinical pharmacology of inhibitors of angiotensin converting enzyme (IACE) in the classification system of ATS is described. Clinical classification, pharmacokinetics and peculiarities of drugs of this group are submitted. Indications for use and features of use of ACE inhibitors in a therapeutic clinic are considered. The emphases of this group of drugs are placed for hypertension, heart failure and ischemic heart disease. The primary contraindications, emphases of interaction with other drugs, side effects and symptoms of overdose are given.